2007
DOI: 10.1149/1.2779073
|View full text |Cite
|
Sign up to set email alerts
|

In-situ FTIR Study of Atomic Layer Deposition (ALD) of Copper Metal Films

Abstract: Growth mechanisms of atomic layer deposition of copper films on various substrates using a novel metal precursor [Cu(sBu-amd)]2 and molecular H2 are investigated by in-situ transmission Fourier transform infrared spectroscopy (FTIR). The Cu-precursor reacts with SiO2 and Al2O3 surfaces by forming chemical bonds with the surface. Upon reduction by H2, Cu atoms agglomerate, yielding additional reactive sites for more Cu-precursors. Cu agglomeration is relatively weaker on nitrided Si surfaces. H-terminated Si su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…A study by Dai et al followed the reaction of copper amidinate precursor ([Cu( s Bu-amd)] 2 , Copper (I) di-sec-butylacetamidinate) with several surfaces including H-Si(100). 108 Despite lower reactivity compared to oxide surfaces, this reaction could be easily followed spectroscopically and it was concluded that the initial reaction happened very quickly, within a few seconds of exposure at a substrate temperature of 185 1C. The remaining surface species exhibited CH x stretching modes observed by infrared spectroscopy, confirming incomplete removal of the ligands.…”
Section: Chemical Reactivity and Selectivity Of The Modified Silicon ...mentioning
confidence: 96%
“…A study by Dai et al followed the reaction of copper amidinate precursor ([Cu( s Bu-amd)] 2 , Copper (I) di-sec-butylacetamidinate) with several surfaces including H-Si(100). 108 Despite lower reactivity compared to oxide surfaces, this reaction could be easily followed spectroscopically and it was concluded that the initial reaction happened very quickly, within a few seconds of exposure at a substrate temperature of 185 1C. The remaining surface species exhibited CH x stretching modes observed by infrared spectroscopy, confirming incomplete removal of the ligands.…”
Section: Chemical Reactivity and Selectivity Of The Modified Silicon ...mentioning
confidence: 96%
“…For instance, in the case of copper acetamidinates (Fig. 1), which can be used alternately with hydrogen to deposit Cu films of reasonably good quality, 19,20 our initial studies using temperature programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS) have suggested that alkyl substituents with b hydrogens may be prone to dehydrogenation reactions to produce olefins and surface acetamide moieties (Fig. 2).…”
Section: Deposition Of Metal Filmsmentioning
confidence: 99%
“…A promising family of metal precursors for ALD is that based on amidinates. Amidinates and related complexes (iminopyrrolidinates, guanidinates) have been long known to be stable, and their introduction for chemical vapor deposition (CVD) and ALD uses has also been assessed in years past. , In particular, a number of Cu amidinates have been tested for the deposition of Cu-containing films, , and we and others ,,, have looked in detail at their surface chemistry as well. For instance, temperature-programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS) experiments to characterize the thermal chemistry of copper­(I)– N , N ′-di- sec -butylacetamidinate adsorbed on Ni(110) and Cu(110) single-crystal surfaces have shown a complex chemistry over a wide range of temperatures.…”
Section: Introductionmentioning
confidence: 99%